Backhand smash - Gregson, J. M. (Gregson, J. M. Detective Inspector Peach mysteries., 2016)
"Detective Sergeant Clyde Northcott--DCI Peach's tall, black, powerful protégé--has no interest in joining the snooty Birch Lane Tennis Club. So it is unfortunate for him when committee member Olive Crawshaw decides he would be the perfect talisman for the club's new, and controversial, policy to recruit members from a wider ethnic and social background. Clyde soon finds himself thrust into an exclusive community where his rusty tennis skills are the least of his concerns: for 'exclusive' does not mean moral, and while some of the club's members sail very close to the law, one of two of them go far beyond it. So when a distinguished club member is murdered, a problem arises: how can he and Peach unveil the killer, when almost everyone seemed to want the victim dead? -- Book jacket flap.